Asset portfolios in Africa: Evidence from rural Ethiopia - Christian Rogg (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper considers asset holdings in rural Ethiopia. It shows that households own mostly non-financial assets and that the composition of asset portfolios varies significantly with the household's overall wealth and its exposure to uncertainty. As regards the distribution of assets, inequality is lowest for land holdings and much higher for all other assets. More generally, asset inequality is higher than consumption inequality but, somewhat surprisingly, lower than income inequality. Less surprising is the finding that asset holdings are positively correlated with income and consumption. An analysis of how asset holdings vary with key demographic variables shows that assets increase with the size of the household and the education of the household head. Finally, the paper concludes by exploring the role that assets play in marriage markets in rural Ethiopia. – savings ; asset portfolios ; household wealth ; asset distribution ; poverty ; inequality ; Ethiopia
Keywords: D1; D31; G11; 330; Kapitalanlage; Privater Haushalt; Landbevölkerung; Äthiopien